-(-9t+9)=(4t-29)

Simple and best practice solution for -(-9t+9)=(4t-29) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-9t+9)=(4t-29) equation:


Simplifying
-1(-9t + 9) = (4t + -29)

Reorder the terms:
-1(9 + -9t) = (4t + -29)
(9 * -1 + -9t * -1) = (4t + -29)
(-9 + 9t) = (4t + -29)

Reorder the terms:
-9 + 9t = (-29 + 4t)

Remove parenthesis around (-29 + 4t)
-9 + 9t = -29 + 4t

Solving
-9 + 9t = -29 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-9 + 9t + -4t = -29 + 4t + -4t

Combine like terms: 9t + -4t = 5t
-9 + 5t = -29 + 4t + -4t

Combine like terms: 4t + -4t = 0
-9 + 5t = -29 + 0
-9 + 5t = -29

Add '9' to each side of the equation.
-9 + 9 + 5t = -29 + 9

Combine like terms: -9 + 9 = 0
0 + 5t = -29 + 9
5t = -29 + 9

Combine like terms: -29 + 9 = -20
5t = -20

Divide each side by '5'.
t = -4

Simplifying
t = -4

See similar equations:

| 5.6x+4.7=-2.2x-3.1 | | 10x-23=8x-4 | | 11=-3(4x-5) | | 14=-20+-20a+48+6a | | [SQRT(2x^2+5x+6)]=x | | 40-8k=2(-8k-2)-4 | | x-8.9=-3.3 | | (3)-15=2(3)-8 | | 2(x+3)=2x-57 | | 23t-2=53t-92 | | x-47=-39 | | 78n+100=550 | | 3(x-3)+21=3x+12 | | -5m+4m+2=5m+8 | | 5(x-8)+9=-60 | | 8=-2p-10 | | 4(-8h-8)=-3h+200 | | 6x+21=4x-57 | | 3-4(x-2)-4=-3x-3-6 | | 41=7x-8 | | 6d+10=12d-5 | | -7k-4k=-4k-k-12 | | x+17=3x-3 | | t+30=22 | | (x-3)(x-3)-12=0 | | 5-3n=-6n-13 | | -9-2f=5f-23 | | 7c+3(c-4)=8 | | 111=-12x+15 | | 30-15w=2w-6 | | 2x+2+7=16 | | -2x+4=ax+b |

Equations solver categories